The Churches of Chiloé: a Story of a Journey, Twenty Years After its International Recognition - Gallardo Gastelo, Felipe Eduardo (Revista Historia y Patrimonio, 2022)
Twenty years past since the consecration of the Churches of Chiloe as a World Heritage Site (WHS) it seems a good moment to recall the course starting at their first consideration as research subject at the Faculty of Architecture and Urbanism of the University of Chile, until their international recognition and later management.The goal of this paper is to revise and check the evolution in time of the process of recognition of the churches, studying its components and later development for the case of the WHS. Considerations will be made around the declaration of WHS and also ondifficulties of management associated to the local context.The former, as a way of enriching national experience face to recent and future declarations of World Heritage Sites. Also, as a contribution on viewpoints about how to approach our national cultural heritage.The hypothesis is that both the role of the community and difficulties in processes of rehabilitation of the WHS Churches of Chiloé are historic, having as an expected result the survival of aspects that can be traced up to their origin and consolidation of the cultural heritage.